Anesthetic Management of a Patient with Dilated Cardiomyopathy Undergoing Cerebral Aneurysm Clipping Surgery: A Case Report - Navneh Samagh; Sarita Sah; Gegal Pruthi; Jyoti Sharma (Journal of Neuroanaesthesiology and Critical Care)
Aneurysmal subarachnoid hemorrhage (aSAH) necessitates prompt neurosurgical intervention. However, patients with associated dilated cardiomyopathy (DCM) face higher cardiovascular instability due to sympathetic surge, stunned myocardium, and tendency to arrhythmias secondary to aSAH. We report a case of DCM and ischemic cardiac disease with a 30% ejection fraction, who presented to us with a severe headache associated with vomiting. Noncontrast computed tomography revealed hematoma in the right fronto-temporoparietal and blood in all the ventricles. Cerebral angiography showed a saccular aneurysm at the right middle cerebral artery bifurcation, thus requiring cerebral aneurysm clipping surgery. Anesthetic agents for induction and maintenance were selected and titrated to minimize cardiac depression and also avoiding systemic hypotension. A bilateral scalp block was administered to blunt sympathetic response to scalp pin application and scalp incision. Hemodynamic monitoring was done perioperatively using pulse index continuous cardiac output monitoring. The patient made an uneventful recovery from the surgery. This case highlights the importance of preoperative planning, accurate interpretation of hemodynamic measurements, and appropriate therapeutic responses to optimize outcomes in cerebral aneurysm surgery associated with DCM.